ALPK1 hotspot mutation as a driver of human spiradenoma and spiradenocarcinoma - Mamunur Rashid; Michiel van der Horst; Thomas Mentzel; Francesca Butera; Ingrid Ferreira; Alena Pance; Arno Rütten; Bostjan Luzar; Zlatko Marusic; Nicolas de Saint Aubain; Jennifer S. Ko; Steven D. Billings; et al. (Nature Communications, 2019)
Spiradenoma and cylindroma are skin adnexal tumors that can behave aggressively and undergo malignant transformation. Here, the authors genetically assess a cohort of these adnexal tumours, highlighting recurrent ALPK1 mutations and revealing the genomic landscape of these rare tumours.